Efficient Red Light Emitting Diodes Based on a Zero‐Dimensional Organic Antimony Halide Hybrid (Adv. Mater. 9/2023). Issue 9 (2nd March 2023) - Liu, He; Shonde, Tunde Blessed; Gonzalez, Fabiola; Olasupo, Oluwadara Joshua; Lee, Sujin; Luong, Derek; Lin, Xinsong; Vellore Winfred, J.S. Raaj; Lochner, Eric; Fatima, Iqra; Hanson, Kenneth; Ma, Biwu
Abstract : Organic Metal Halide Hybrids Efficient electroluminescent devices can now be fabricated using solution‐processed thin films based on 0D organic metal halide hybrids (OMHHs). In article number 2209417, Biwu Ma and co‐workers develop a highly luminescent 0D OMHH containing organic semiconducting cations, which successfully addresses the issues of low conductivity and poor energy alignment of existing 0D OMHHs for electrically driven light‐emitting diodes (LEDs).